Workaholism on Job Burnout: A Comparison Between American and Chinese Employees - Cheung, Francis; Tang, Catherine S. K.; Lim, Matthew Sheng Mian; Koh, Jie Min (Frontiers in Psychology, 2018)
Past research frequently reports significant relation between workaholism and job burnout, and some studies further indicate workaholism varies across countries. Surprisingly, there is no study that directly examines whether country moderates the workaholism-burnout association. To address this research question, we have collected independent work samples from two culturally diverse countries, namely the People’s Republic of China and the United States. A total of 2243 participants (1243 American respondents and 1000 Chinese respondents) were recruited. Preliminary group comparison suggested that there were statistical differences among participants from different industries on the key variables, including workaholism, job demands, autonomy and emotional exhaustion. Therefore, we have divided our participants into three subsamples [i.e., (1) natural resources, mining and construction industry, (2) manufacturing industry, and (3) service industry] and separate analyses were conducted. In the moderated regression analyses, workaholism significantly predicted two dimensions of job burnout, namely emotional exhaustion and depersonalization, even when job demand and job autonomy were controlled. Finally, although two significant moderating effects were found, there was a lack of consistent empirical support to the hypothesized moderating effect of country on workaholism-burnout association. Implications and limitations were discussed.